The psychological and physiological preparation of elite freestyle wrestlers - Kuvanov V.A.; Mikhaylovskiy S.P.; Zaytsev A.V.; Davydov M.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to examination of the impact of ideomotor exercises on the performance of highly skilled freestyle wrestlers in competition. Methods and structure of the study. The study involved the analysis and synthesis of literary sources, conducting a pedagogical experiment, conducting psychophysiological tests, and applying mathematical statistical methods. The research was conducted in the comprehensive school of high sports skills of St. Petersburg. The participants were wrestlers aged between 16 and 29. The group consisted of 34 freestyle wrestlers with varying levels of training. The wrestlers were divided into two groups. The first group included highly skilled athletes, such as candidates and masters of sports (16 individuals), while the second group consisted of wrestlers with II and III categories (18 individuals). In the second and third stages, the skilled wrestlers were divided into two groups: a control group and an experimental group. The psychophysiological characteristics were examined through tests. The study was based on the methodology of test control, which included tapping tests (E.P. Ilyin, 1983), reflexometry, and tremometry. Results and conclusions. The application of the experimental approach yielded the following outcomes: The wrestlers in the experimental group demonstrated significant improvements in two out of the three psychophysiological characteristics. The study revealed a correlation between psychophysiological characteristics and the level of psychological and physical strain during training. A method for enhancing the psychophysiological characteristics of athletes was developed.